Analisis Kondisi Sosial, Ekonomi, dan Politik Negara Belanda yang Merupakan Bagian Dari G10 - Natalis Christian; Manurung, Nova Sari; Helvida Githa Putri Br Purba (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study reviews the social, economic and political conditions of the Netherlands as part of the G10. This study aims to provide information and explanations regarding the social, economic, and political conditions from various sides of the Netherlands. The social conditions of the Netherlands are in the form of geographic location, demographic population, poverty rate, and unemployment rate. Economic conditions in the form of Gross Domestic Product, international trade, inflation rates, exchange rates, and wage levels. Political conditions in the form of government composition, political climate, and foreign relations. With a qualitative research method, it can provide an overview of the contents of this study. From the studies that have been carried out, it is found that there are conditions that underlie the Netherlands can be influenced by various factors so that there is an increase or decrease in some of these conditions. With this research, the implications that can be given are with information and insights on research for related parties and can evaluate the performance of each country with social, economic, and political aspects.